TERT rs2736100 and TERC rs16847897 genotypes moderate the association between internalizing mental disorders and accelerated telomere length attrition among HIV+ children and adolescents in Uganda - Allan Kalungi; Eugene Kinyanda; Jacqueline S. Womersley; Moses L. Joloba; Wilber Ssembajjwe; Rebecca N. Nsubuga; Pontiano Kaleebu; Jonathan Levin; Martin Kidd; Soraya Seedat; Sian M. J. Hemmings (BMC, 2021)
Abstract Background Internalizing mental disorders (IMDs) (depression, anxiety and post-traumatic stress disorder) have been associated with accelerated telomere length (TL) attrition; however, this association has not been investigated in the context of genetic variation that has been found to influence TL. We have previously reported an association between IMDs and accelerated TL attrition among Ugandan HIV+ children and adolescents. This study investigated the moderating effects of selected single nucleotide polymorphisms in the telomerase reverse transcriptase gene (TERT) (rs2736100, rs7726159, rs10069690 and rs2853669) and the telomerase RNA component gene (TERC) (rs12696304, rs16847897 and rs10936599) on the association between IMDs and TL, among Ugandan HIV+ children (aged 5-11 years) and adolescents (aged 12-17 years). Results We found no significant interaction between IMDs as a group and any of the selected SNPs on TL at baseline. We observed significant interactions of IMDs with TERT rs2736100 (p = 0.007) and TERC rs16847897 (p = 0.012), respectively, on TL at 12 months. Conclusions TERT rs2736100 and TERC rs16847897 moderate the association between IMDs and TL among Ugandan HIV+ children and adolescents at 12 months. Understanding the nature of this association may shed light on the pathophysiological mechanisms underlying advanced cellular aging in IMDs.